Stream IMC - how to leverage sogrape´s wine business in the Uk: promotion - Domingos, Catarina Ribeiro Agostinho Gomes (2022)
The aim of this individual assignment was to determine the most appropriate brand activations (including promotions, such as trade promotions and consumer promotions) to be utilized in the re-launch of the Casa Ferreirinha fine wines -Vinha Grande, Callabriga and Quinta da Leda. As one of the main objectives of the marketing plan was to increase distribution, trade promotions were emphasized. The proposed strategy also includes consumer promotions (sampling) and experiential marketing.